PREFERNSI MASYARAKAT TERHADAP SAGU SEBAGAI SUMBER PANGAN MASYARAKAT SUKU MALIND YEINAN DI KAMPUNG POO, DISTRIK JAGEBOB – MERAUKE - Ika Wahyu Octaviani Putri; Maria Maghdalena Diana Widiastuti; Riza Fachrizal (Musamus Journal of Agribusiness, 2018)
The research aims to analyze the preferences of the local Papuan people of Yeinan towardssago consumption and analyze any preferences that are more dominant in the selection of sagocommodities as local food. The study was conducted in Poo Village, Jagebob District, MeraukeRegency, for two (2) months, namely from May to June 2018. The population in this study wasthe entire community of Poo village. The technique of determining samples is done randomly( Random Sampling ), data analysis is done by qualitative and quantitative analysis methodsusing multiple linear regression analysis. The results of the regression analysis showed thatpeople's preference for sago consumption (Y): at the 5% level based on taste (X 1 ) with asignificant value of 0.107 did not significantly influence the amount of sago consumption,processing variable (X 2 ) with a significant value of 0.440 no significantly affect the amount ofconsumption of sago, and the variable resistance (X 3) deng an significant values of 0, 5 58 didnot significantly affect the amount of consumption of sago. So from the results of this studythat people's preference for sago consumption is not influenced by the variables of taste,processing, and endurance. Where the R value of 0.212 is obtained, which is low and the Rsquare value is 0.045 or 4,5 %.Keywords: Preference, Sago, Yeinan Tribe